PELATIHAN “CERDAS BER INTERNET” BAGI ORANG TUA DI DESA BURNEH BANGKALAN - Drajat Wicaksono; Yuliana Rakhmawati; Nikmah Suryandari (LP2M Universitas Hasanuddin, 2021)
Abstract. The activity of digital literacy was carried out in the form of counseling about smart internet for parents in Burneh village, Bangkalan. This activity aims to provide knowledge and understanding regarding the importance of parental assistance to children in accessing the internet, provide insight into the negative impacts of technological developments, especially information circulating in cyberspace, provide knowledge about attitudes anticipatory towards various negative impacts caused by internet media and other social media, providing knowledge and understanding of the importance of family communication as a provision for parenting and mentoring of parents to children. The method used in this activity is the planning stage, pre survey of the location of activities, preparation of instruments for community service activities, coordination and resolution of administrative problems, counseling about healthy internet use. Counseling is important, especially for the target group, namely parents. Parents hold an important role in interaction in the family. The pattern of parenting and mentoring for parents is expected to reduce the negative impact of unhealthy internet use. The result of this activity is an increase in parents' knowledge and understanding of digital literacy in families, especially smart internet using. Abstrak. Kegitan literasi digital ini dilakukan dalam bentuk penyuluhan tentang cerdas berinternet bagi orang tua di desa Burneh Bangkalan. Kegiatan ini bertujuan untuk memberikan pengetahuan dan pemahaman menegenai pentingnya pendampingan orang tua pada bagi anak dalam mengakses internet, memberikan wawasan mengenai dampak negatif dari perkembangan teknologi, khususnya informasi yang beredar di dunia maya, memberikan pengetahuan mengenai sikap antisipatif terhadap beragam dampak negatif yang ditimbulkan oleh media internet dan media sosial lainnya, memberikan pengetahuan dan pemahaman tentang pentingnya komunikasi keluarga sebagai bekal pengasuhan dan pendampingan orang tua pada anak. Metode yang dilakukan dalam kegiatan ini adalah tahap perencanaan, pra survei lokasi kegiatan, penyusunan instrumen kegiatan pengabdian masyarakat, koordinasi dan penyelesaian masalah administrasi, penyuluhan tentang penggunaan internet secara sehat. Penyuluhan penting dilakukan khususnya kepada kelompok sasaran yaitu para orang tua. Karena orang tua memegang peran penting dalam interaksi dalam keluarga. Pola pengasuhan dan pendampingan orang tua, diharapkan mampu mengurangi dampak negatif penggunaan internet yang kurang sehat. Hasil dari kegiatan ini adalah adanya peningkatan pengetahuan dan pemahaman orang tua mengenai literasi digital dalam keluarga, khususnya berinternet secara sehat.